Hydrogel coating zinc negative electrode with long cycle life and high utilization rate, preparation method and application thereof, and aqueous zinc-iodine battery
By preparing a dual network hydrogel coating on the surface of zinc foil, the problems of short cycle life of zinc anode and low zinc utilization rate of water-based zinc-iodine batteries are solved, and the long cycle life and high zinc utilization rate of the battery are achieved, which improves the stability and energy density of the battery.
Patent Information
- Application Number
- CN202411685479.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2044-11-22
AI Technical Summary
Water-based zinc-iodine batteries have problems such as short cycle life of zinc negative electrode and low zinc utilization rate, resulting in poor battery stability and low energy density.
Prepare a dual network hydrogel coating containing zinc oxide nanoparticles, sodium alginate and polyacrylamide in situ on the surface of zinc foil to optimize zinc nucleation and deposition behavior, block the diffusion of water molecules and polyiodides, and reduce side reactions.
It realizes the long cycle life and high zinc utilization rate of aqueous zinc-iodine batteries, improves the stability and energy density of the battery, and has the advantages of low cost, safe and environmentally friendly, and large-scale preparation.
Smart Images

Figure HDA0005149308410000011 
Figure HDA0005149308410000012 
Figure HDA0005149308410000013
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of new energy batteries, and in particular to a long cycle life, high utilization rate hydrogel coated zinc negative electrode, a preparation method and application thereof, and an aqueous zinc-iodine battery. Background Art
[0002] To meet the requirements for the integration of renewable energy sources, reliable and low-cost electrochemical energy storage systems are in high demand. Among all the available candidate materials, zinc metal and aqueous electrolytes have shown their excellent performance due to their special properties, including a considerable capacity (5855 mAh mL -1 ), suitable redox potential (-0.76Vvs.SHE), non-toxic and intrinsically safe, aqueous zinc batteries are considered to be a promising electrochemical energy storage system.
[0003] Aqueous zinc-iodine (Zn-I2) batteries have rich iodine resources and high theoretical capacity (about 211 mAh g -1 ), as well as a high voltage platform of about 1.38V, have attracted widespread attention from researchers. However, aqueous Zn-I2 batteries themselves have the problem of short cycle life. Specifically, zinc dendrite growth, hydrogen evolution reaction and by-products lead to poor reversibility of zinc metal negative electrode. In addition, the I2 positive electrode conversion reaction will form polyiodides, which can be dissolved in the aqueous electrolyte and diffuse to the zinc negative electrode, causing loss of I2 positive electrode active materials and zinc corrosion, affecting the battery cycle stability. In order to solve these problems, researchers often use excess zinc to ensure a continuous supply of zinc negative electrode active materials, which results in extremely low zinc utilization at the negative electrode (usually less than 10%). At the same time, the use of excessive zinc increases the cost of the battery and reduces the actual energy density. Therefore, improving the stability of the zinc negative electrode and the utilization of zinc has become an urgent problem to be solved in this field. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a long cycle life, high utilization rate hydrogel coated zinc negative electrode and a preparation method thereof. A double network hydrogel coating containing zinc oxide nanoparticles, sodium alginate and polyacrylamide is prepared in situ on the surface of zinc foil to achieve rapid and uniform zinc ion transmission and good mechanical stability, while blocking the diffusion of water molecules and polyiodides to the negative electrode, significantly reducing the side reactions at the interface between the zinc negative electrode and the electrode electrolyte. In order to solve the problem of low zinc utilization and short cycle life of aqueous zinc-iodine batteries, the aqueous zinc-iodine battery of the present invention has a long cycle life, high zinc utilization, and has the advantages of low cost, safety, environmental protection, and large-scale preparation.
[0005] The above technical objectives of the present invention are achieved through the following technical solutions:
[0006] The invention provides a long cycle life and high utilization rate hydrogel coated zinc negative electrode, comprising a zinc foil and a double network hydrogel coating containing zinc oxide nanoparticles, sodium alginate and polyacrylamide and covering the surface of the zinc foil.
[0007] The present invention also provides a method for preparing a hydrogel-coated zinc negative electrode with a long cycle life and high utilization rate, comprising the following preparation steps:
[0008] (1) adding sodium alginate and polyacrylamide in a certain proportion into deionized water and stirring to dissolve;
[0009] (2) adding zinc oxide nanoparticles and continuing to stir and disperse to obtain a uniform dispersion;
[0010] (3) The above dispersion is scraped onto the surface of zinc foil with a certain thickness, and then placed in an aqueous solution containing zinc salt for cross-linking to obtain a double network hydrogel coated zinc negative electrode.
[0011] The present invention is further configured as follows: the mass fraction of sodium alginate in the above dispersion is 1% to 5%, the molecular weight of the polyacrylamide used is 5 million to 20 million, the mass fraction is 0.5% to 3%, the particle size of the zinc oxide nanoparticles used is 50 to 500 nanometers, the mass fraction is 0.1% to 2%;
[0012] The present invention is further configured as follows: the thickness of the zinc foil used is 10 to 500 μm, the thickness of the dispersion coating is 20 to 200 μm. The zinc salt used is a mixture of one or more of zinc sulfate, zinc trifluoromethanesulfonate, zinc chloride, and zinc acetate, and the zinc salt concentration is 0.5 to 3.0 mol·L -1 , soaking time 0.1~12h.
[0013] The present invention is further configured as follows: the zinc salt used is a mixture of one or more of zinc sulfate, zinc trifluoromethanesulfonate, zinc chloride, and zinc acetate, and the zinc salt concentration is 0.5 to 3.0 mol·L -1 The soaking time is 0.1 to 12 hours.
[0014] Another object of the present invention is to provide an aqueous zinc-iodine battery, characterized in that it consists of a positive electrode, a negative electrode, a separator, and an electrolyte, the negative electrode uses the above-mentioned hydrogel-coated zinc negative electrode, and preferably, the separator uses a cellulose paper separator.
[0015] Compared with the prior art, the present invention has the following beneficial technical effects:
[0016] The present invention prepares a double-network hydrogel coating containing zinc oxide nanoparticles, sodium alginate and polyacrylamide in situ on the surface of zinc foil, optimizes zinc nucleation and deposition behavior, effectively inhibits side reactions and zinc dendrite growth, and achieves high zinc utilization and excellent long-cycle stability of aqueous zinc-iodine batteries. The assembled Zn||Zn symmetric battery has a current density of 2 mA cm -2 Under the conditions of 60% zinc utilization, it shows a cycle life of more than 1600 hours. The aqueous zinc-iodine battery prepared with this negative electrode has a cycle life of more than 12,000 times and a capacity retention rate of up to 90% at a current density of 5C.
[0017] The hydrogel-coated zinc negative electrode and preparation method thereof provided by the present invention have simple process, low cost, high safety, and are conducive to large-scale production. The assembled aqueous zinc-iodine battery has high capacity and long cycle life, and can be widely used in electric vehicles and large-scale energy storage fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The zinc-zinc symmetric battery assembled with the zinc negative electrode containing the hydrogel coating prepared in Example 10 of the present invention was heated to a current density of 2 mA·cm -2 ,, Cyclic performance under the condition of 60% zinc utilization;
[0019] Figure 2 The zinc-zinc symmetric battery assembled with the zinc negative electrode containing the hydrogel coating prepared in Comparative Example 1 of the present invention was heated to a current density of 2 mA·cm -2 ,, Cyclic performance under the condition of 60% zinc utilization
[0020] Figure 3 The zinc-zinc symmetric battery assembled with the zinc negative electrode containing the aqueous gel coating prepared in Example 10 of the present invention was heated to a current density of 4 mA·cm -2 ,, Cyclic performance under the condition of 60% zinc utilization;
[0021] Figure 4 The zinc-zinc symmetric battery assembled with the zinc negative electrode containing the hydrogel coating prepared in Comparative Example 1 of the present invention was heated to a current density of 4 mA·cm -2 ,, Cyclic performance under the condition of 60% zinc utilization;
[0022] Figure 5 The charge and discharge curves of the zinc-iodine battery prepared in Example 11 of the present invention at different rates;
[0023] Figure 6 Comparison of the cycle performance of the zinc-iodine battery prepared in Example 11 of the present invention and Comparative Example 2 at a rate of 5C;
[0024] Figure 7Comparison of the cycle performance of the zinc-iodine battery prepared in Example 11 of the present invention and Comparative Example 2 at a rate of 10C; DETAILED DESCRIPTION
[0025] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0026] Embodiment 1:
[0027] A composite hydrogel coating containing zinc oxide nanoparticles, the specific preparation steps are as follows:
[0028] (1) Preparation of a polymer dispersion containing zinc oxide nanoparticles:
[0029] 4% sodium alginate and 1% polyacrylamide (molecular weight 14 million) were added to deionized water, stirred and dissolved to obtain a transparent solution, and then 1% zinc oxide nanoparticles (particle size 100 nm) were added, and stirring was continued to uniformly disperse the zinc oxide nanoparticles.
[0030] (2) Preparation of hydrogel coating:
[0031] The above dispersion was evenly scraped onto a smooth PTFE plate with a scraper. The scraping thickness was set to 200 μm. Then the scraped coating was heated to a concentration of 0.5 mol·L -1 The polymer was immersed in a zinc sulfate solution for 0.5 h to cross-link the polymer with zinc ions to form a polymer hydrogel coating.
[0032] Embodiment 2:
[0033] A composite hydrogel coating containing zinc oxide nanoparticles, the specific preparation steps of which refer to Example 1, except that the mass fraction of polyacrylamide in the dispersion is 2%.
[0034] Embodiment 3:
[0035] A composite hydrogel coating containing zinc oxide nanoparticles, the specific preparation steps of which refer to Example 1, except that the mass fraction of polyacrylamide in the dispersion is 3%.
[0036] Embodiment 4:
[0037] A composite hydrogel coating containing zinc oxide nanoparticles, the specific preparation steps of which refer to Example 1, except that the mass fraction of polyacrylamide in the dispersion is 4%.
[0038] Embodiment 5:
[0039] A composite hydrogel coating containing zinc oxide nanoparticles. The specific preparation steps refer to Example 1, except that the mass fraction of polyacrylamide in the dispersion is 2%, and the mass fraction of zinc oxide nanoparticles is 0.5%.
[0040] Embodiment 6:
[0041] A composite hydrogel coating containing zinc oxide nanoparticles. The specific preparation steps refer to Example 1, except that the mass fraction of polyacrylamide in the dispersion is 2%, and the mass fraction of zinc oxide nanoparticles is 2%.
[0042] Embodiment 7:
[0043] A composite hydrogel coating containing zinc oxide nanoparticles. The specific preparation steps refer to Example 1, except that the mass fraction of polyacrylamide in the dispersion is 2%, and the mass fraction of zinc oxide nanoparticles is 3%.
[0044] Embodiment 8:
[0045] A composite hydrogel coating containing zinc oxide nanoparticles, the specific preparation steps are as described in Example 1, except that the mass fraction of polyacrylamide in the dispersion is 2%, the mass fraction of zinc oxide nanoparticles is 2%, and the zinc salt solution used for immersion is 0.5 mol·L -1 Zinc trifluoromethanesulfonate solution.
[0046] Embodiment 9:
[0047] A composite hydrogel coating containing zinc oxide nanoparticles, the specific preparation steps are as described in Example 1, except that the mass fraction of polyacrylamide in the dispersion is 2%, the mass fraction of zinc oxide nanoparticles is 2%, and the zinc salt solution used for immersion is 0.5 mol·L -1 Zinc acetate solution.
[0048] The room temperature ionic conductivity and mechanical strength of the composite hydrogels prepared in Examples 1 to 9 were tested, and the results are shown in Table 1.
[0049] Table 1. Test results of electrical conductivity and mechanical properties of Examples 1 to 9.
[0050] serial number Conductivity (mS / cm) Tensile stress(kPa) Tensile strain (%) Example 1 4.9 36.2 71 Example 2 16.2 21.7 73 Example 3 15.5 15.6 84 Example 4 18.2 9.8 66 Example 5 11.3 19.8 80 Example 6 26.2 17.1 72 Example 7 22.4 11.4 68 Example 8 24 23.5 75 Example 9 20.6 20.6 73
[0051] It can be seen from Table 1 that the composite hydrogel coatings prepared in Examples 1 to 9 all exhibited high ionic conductivity and mechanical strength, among which the composite hydrogel coating prepared in Example 6 had an ionic conductivity of up to 26.2 mS / cm while maintaining good mechanical strength.
[0052] Embodiment 10:
[0053] A long cycle life and high utilization rate hydrogel coated zinc negative electrode, the specific preparation steps are as follows:
[0054] (1) Preparation of a polymer dispersion containing zinc oxide nanoparticles:
[0055] 4% sodium alginate and 2% polyacrylamide (molecular weight 14 million) were added to deionized water, stirred and dissolved to obtain a transparent solution, and then 2% zinc oxide nanoparticles (particle size 100 nm) were added, and stirring was continued to uniformly disperse the zinc oxide nanoparticles.
[0056] (2) Preparation of hydrogel-coated zinc negative electrode:
[0057] The above dispersion was evenly coated on the surface of a zinc foil with a thickness of 20 μm by a scraper, and the coating thickness was set to 100 μm. Then the zinc foil coated with the above dispersion was heated to a concentration of 0.5 mol·L -1 The polymer was immersed in a zinc sulfate solution for 0.5 h to cross-link the polymer with zinc ions to form a polymer hydrogel coating.
[0058] Comparative Example 1:
[0059] Bare zinc foil, i.e. bare zinc anode without hydrogel coating
[0060] The hydrogel-coated negative electrode prepared in Example 10 was used to assemble a zinc-zinc symmetric battery and its cycle stability was tested. Figure 1 As shown, at a current density of 2 mA cm -2 、Capacity 6.97mAh·cm -2 Under the condition of 60% zinc utilization, the assembled Zn||Zn symmetric battery showed a cycle life of more than 1600 hours, while the cycle life of the Zn||Zn symmetric battery assembled with bare zinc foil in comparative example 1 was only 130 hours under the same conditions ( Figure 2 );like Figure 3 As shown in the figure, when the current density increases to 4 mA cm -2 The Zn||Zn symmetric battery assembled in Example 10 can still stably cycle for more than 920 hours, and the cycle life is much longer than that of the zinc negative electrode without hydrogel coating in Comparative Example 1 (70 hours, Figure 4 ).
[0061] Embodiment 11:
[0062] An aqueous zinc-iodine battery, the specific preparation steps are as follows:
[0063] (1) Preparation of iodine-activated carbon positive electrode:
[0064] Activated carbon and solid iodine particles (mass ratio of 1:1) were ground in a mortar to make them fully mixed, and then transferred to a sealed reagent bottle and heated at 60°C for 12 hours. After cooling, iodine-activated carbon, conductive carbon black (Super P), and acrylonitrile multipolymer aqueous dispersion (LA133) binder were mixed in a mass ratio of 8:1:1 and deionized water was added and stirred to form a uniform slurry, which was then coated on graphite paper and dried in an oven at 40°C and cut into circular electrodes with a diameter of 12 mm.
[0065] (2) Preparation of zinc negative electrode:
[0066] The zinc negative electrode prepared in Example 10 was cut into circular electrode pieces with a diameter of 14 mm to obtain a zinc negative electrode containing a hydrogel coating.
[0067] (3) Preparation of electrolyte:
[0068] Add zinc sulfate heptahydrate into deionized water and stir to dissolve to obtain a concentration of 2 mol·L -1 Zinc sulfate solution is used as the electrolyte.
[0069] (3) Assembling aqueous zinc-iodine battery:
[0070] A CR2032 button-type aqueous zinc-iodine battery was obtained by packaging the battery in the order of a positive electrode shell, a positive electrode sheet, a separator, a hydrogel-coated zinc negative electrode, a gasket, a spring, and a negative electrode shell using a button battery packaging machine.
[0071] Comparative Example 2:
[0072] An aqueous zinc-iodine battery, the specific preparation steps are the same as those in Example 11, except that a bare zinc foil without a hydrogel coating is used as the negative electrode.
[0073] From the attached Figure 5 It can be seen that the aqueous zinc-iodine battery prepared in Example 11 has high capacity and excellent rate performance. At a current density of 0.5C (1C = 211 mA g -1 ) The battery has a specific capacity of up to 191 mAh g -1 , still has 152mAh·g at 10C current density -1 Specific capacity.
[0074] From the attached Figure 6 and attached Figure 7 It can be seen that the aqueous zinc-iodine battery prepared in Example 11 has an ultra-long cycle life, with a capacity retention rate of up to 90% after more than 12,000 cycles at a current density of 5C, and a capacity retention rate of 80% after 14,000 cycles at a current density of 10C, which is far longer than the aqueous zinc-iodine battery with bare zinc foil as the negative electrode in Comparative Example 2.
[0075] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A long cycle life and high utilization rate hydrogel coated zinc negative electrode, characterized in that: The invention comprises a zinc foil and a double network hydrogel coating containing zinc oxide nanoparticles, sodium alginate and polyacrylamide and covering the surface of the zinc foil.
2. The method for preparing a long cycle life and high utilization rate hydrogel-coated zinc negative electrode according to claim 1, characterized in that: The method comprises the following preparation steps: Step (1) adding sodium alginate and polyacrylamide in a certain proportion into deionized water and stirring to dissolve; Step (2) adding zinc oxide nanoparticles and continuing to stir and disperse to obtain a uniform dispersion; Step (3) coating the above dispersion on the surface of zinc foil with a certain thickness, and then placing it in an aqueous solution containing zinc salt for cross-linking to obtain a double network hydrogel coated zinc negative electrode.
3. The method for preparing a hydrogel-coated zinc negative electrode according to claim 2, characterized in that: The mass fraction of sodium alginate in the above dispersion is 1% to 5%, and the molecular weight of the polyacrylamide used is 5 million to 20 million, and the mass fraction is 0.5% to 3%.
4. The method for preparing a hydrogel-coated zinc negative electrode according to any one of claims 2 to 3, characterized in that: The hydrogel is filled with zinc oxide nanoparticles, the particle size of the zinc oxide nanoparticles used is 50 to 500 nanometers, and the mass fraction is 0.1% to 2%.
5. The method for preparing a hydrogel-coated zinc negative electrode according to claim 4, characterized in that: The thickness of the zinc foil used is 10-500 μm, and the thickness of the dispersion coating is 20-200 μm.
6. The method for preparing a hydrogel-coated zinc negative electrode according to any one of claim 4, characterized in that: The zinc salt used is a mixture of one or more of zinc sulfate, zinc trifluoromethanesulfonate, zinc chloride, and zinc acetate, and the zinc salt concentration is 0.5 to 3.0 mol·L -1 The soaking time is 0.1 to 12 hours.
7. An aqueous zinc-iodine battery, characterized in that: The invention is composed of a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the negative electrode uses the hydrogel-coated zinc negative electrode according to any one of claims 2, 3 or 6.
8. An aqueous zinc-iodine battery, characterized in that: The invention is composed of a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the negative electrode uses the hydrogel-coated zinc negative electrode as claimed in claim 4.
9. An aqueous zinc-iodine battery, characterized in that: The invention is composed of a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the negative electrode uses the hydrogel-coated zinc negative electrode as claimed in claim 5.
Citation Information
Patent Citations
Preparation and application of metal zinc negative electrode with functional nano material modification layer
CN113488607A
Inorganic composite hydrogel electrolyte membrane and preparation and application thereof in aqueous zinc ion battery
CN113921793A
Negative plate, preparation method thereof and zinc-based battery
CN115911242A
Application of alginate-carbon-based additive hydrogel coating resistant to corrosion of high-concentration bromine in protection of zinc electrode of filmless zinc-bromine battery
CN118970042A